Effect of high frequency harmonic voltage on the performance of line start permanent magnet synchronous motor. Issue 2 (1st April 2019) - Qiu, Hongbo; Hu, Kaiqiang; Yi, Ran; Yanqi, Wei
Abstract : Purpose: A large number of high-frequency harmonic voltages exist in the output voltage of the inverter, which will affect the performance of the motor. The purpose of this paper is to obtain the influence of high frequency harmonic voltage on the performance of the line start permanent magnet synchronous motor (LSPMSM) and reveal the mechanism of influence. The research results can provide help for the design of LSPMSM driven by inverter drives. Design/methodology/approach: First, the actual output voltage data of the inverter is collected, and then the fundamental voltage and high frequency harmonic voltage data can be obtained by performing the fast Fourier transformation method on the voltage data. Second, the finite element model is established. During the finite element calculation, the obtained fundamental voltage and the main harmonic voltage components are used as the voltage source. To research the effect of high frequency harmonic voltage on the performance of motor, a reference group without high frequency harmonic voltage is set up, which is used to compare and analyze the effect of high-frequency harmonics on the performance of the motor. To verify the correctness of the model, a prototype based on the model parameters is manufactured, and then the back EMF experiment and load experiment are performed. The test data and calculation results are compared and analyzed. Findings: The coupling relationship between high frequency time harmonic magnetic field and low frequency space harmonic magnetic field is obtained. The stator copper loss and rotor eddy-current loss are calculated and analyzed under normal supply voltage and abnormal supply voltage, and the influence mechanism is revealed Originality/value: The coupling relationship between high frequency time harmonic magnetic field and low frequency space harmonic magnetic field is obtained. The sensitivity of the high frequency harmonic voltage to the stator copper loss and rotor eddy-current loss is obtained, and the mechanism of losses change is revealed.